The Effect of Operational and Financial Leverage on Economic Performance Indicators: Evidence from industrial companies listed on the Amman Stock Exchange - Saraireh, Dr. Shadi Arshid Muslim (The journal of contemporary issues in business and government, 2021)
The aim of study was to examine the impact of the operational and financial leverage on the economic performance indicators in the industrial companies listed on the Amman Stock Exchange (ASE). The financial reports for the financial statements of the industrial companies were collected during the period of five years 2014-2018 for the listed companies whose shares are in the Amman Stock Exchange, and the study population were 62 Industrial companies until 31st December 2018. The sample of the study population was presented by 13 companies distributed over four industrial sectors such as Tobacco and Cigarettes, Medicine and Medical Industries, Chemicals, Food and Beverages. This study depends on data processing (Panel Data) using the STATA program. The results of the study showed that the economic value-added came in a medium degree for the industrial investment companies. Meanwhile, the market value-added came as a second order, there was no statistically significant effect of the operational and financial leverage on the economic value- added and the market value-added in the Jordanian industrial companies listed on the Amman Stock Exchange (ASE). The Study recommended the increase of caution when using loans for financing due to the effect of increasing operational risks in industrial companies.